Marriage Agreements as a Form of Legal Protection For Parties To a Marriage - Astuti, Rita Bayu; Ali, Moh.; Rato, Dominikus (PT Matra Cendikia Abadi, 2025)
This research is reviewed from the Marriage Law and Compilation of Islamic Law. Positive Law and Islamic Law only recognize open monogamous marriages, but it does not rule out the possibility for a husband to have a polygamy marriage with the conditions as stated in Article 4 paragraph (2) of the Marriage Law by submitting an application to the Religious Court. The problem formulation is first, how is the application of shared assets in polygamy marriages in Indonesia? Second, how is the legal protection of assets in the polygamy marriage agreement? This research is a normative-juridical study with the aim of finding the coherent truth. The legal force of a marriage agreement is binding not only upon the spouses who execute it but also upon related third parties, provided that the element of publicity has been satisfied. Where a marriage agreement is executed in fulfillment of the validity requirements for agreements in accordance with applicable statutory regulations, ratified by a Marriage Recording Officer or a notary, and recorded by the Marriage Recording Officer, said marriage agreement possesses legal force equivalent to that of an authentic deed. A marriage agreement executed via a notarial deed also constitutes a protective measure ensuring that the agreement becomes an authentic deed possessing perfect probative force to safeguard the rights of the contracting parties as well as third parties. Furthermore, related third parties are entitled to claim compensation should the marriage agreement be executed or amended with the intent to prejudice said third parties.